Amelia rules!. Funny stories - Gownley, Jimmy (Renaissance Press, 2006)
Amelia McBride faces more changes and challenges after her family moves once again, her new friend Trish hides a terrible secret, and superhero-wannabe Reggie vows to destroy the evil Legion of Steves.